Growth and Bone Mineral Accretion During Puberty in Chinese Girls: A Five-Year Longitudinal Study - Kun, Zhu; Heather, Greenfield; Qian, Zhang; Xueqin, Du; Guansheng, Ma; Leng, Huat Foo; Chris, T Cowell; David, R. Fraser (American Society for Bone and Mineral Research, 2007)
There are few longitudinal data on bone development during puberty in children with low calcium intake. This 5-yr longitudinal study showed that, in Chinese girls, the mean apparent calcium retention efficiency during puberty was 40.9%, PHV occurred at 3–0 yr before menarche, and peak bone mineral accretion occurred 1 yr later than PHV. Chinese girls have high calcium retention efficiency during puberty. There are few longitudinal data on bone development during puberty in children with low dietary calcium intake. The aim of this study was to examine the rate of growth and bone mineral accretion and study the predictors of total body BMC during puberty in a 5-yr longitudinal study with Chinese girls. Materials and Methods: Ninety-two girls, 9.5–10.5 yr of age at baseline, from the unsupplemented control group of a school milk intervention trial were included in this analysis. Data on anthropometric measurements, total body BMC as assessed by DXA, and calcium intake as assessed by a 3-day food record were obtained at baseline and 1, 2, 4, and 5 yr.